If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4p-9=3p-5
We move all terms to the left:
4p-9-(3p-5)=0
We get rid of parentheses
4p-3p+5-9=0
We add all the numbers together, and all the variables
p-4=0
We move all terms containing p to the left, all other terms to the right
p=4
| 129=y+9 | | 7-11c=11 | | 8=4r | | 3×43=y+9 | | p2=0 | | −27=8x−5 | | 241=187-w | | f=3.4=2.1 | | 4x+2=2x-2+2x | | 5x+2=5x+11 | | 9x+8=x+64 | | 3(x-4)-5x=-2 | | 3.1x+26.7/72.083=26.93 | | 6^2+3^2=c | | X^2=4i^2 | | T=2s+3.15 | | -4=8+2v | | 7(5x+10)=35x-5 | | 2/y+3+5/y-4=7/y+5 | | 7n+3=3n+23 | | 6x-4/4=12 | | -8+(1/3)y=2 | | (n-2)(n-1)n=336 | | 16-x=269 | | 11x+2=11x-10 | | (241895-8*y)/21+8y=241895 | | 6t+1/6t-5=2t+4/2t-7 | | 12x+9x=x | | 5v+9=99 | | X×10+22=x×3+148 | | 4x+29=x+8 | | -24=-6+6k |